2009
DOI: 10.1021/ma900394n
|View full text |Cite
|
Sign up to set email alerts
|

Deformation-Induced Mobility in Polymer Glasses during Multistep Creep Experiments and Simulations

Abstract: Optical photobleaching experiments and molecular dynamics computer simulations were used to investigate changes in segmental mobility during tensile creep deformation of polymer glasses. Experiments were performed on lightly cross-linked PMMA, and the simulations utilized a coarse-grained model. For both single-step and multistep creep deformations, the experiments and simulations show remarkably similar trends, with changes of mobility during deformation exceeding a factor of 100. Both experiment and simulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

30
148
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 117 publications
(179 citation statements)
references
References 43 publications
30
148
1
Order By: Relevance
“…N = 500 chains orient nearly affinely during strain: ǫ ef f ≃ǫt, while short chains orient much less. The solid lines are far more consistent with both experiments [3][4][5] and simulations [6,7], which show relaxation slows dramatically upon cessation of active deformation. Figure 3 shows simulation data for ǫ ef f (t) under the same procedure of compression followed by constantstrain relaxation.…”
Section: E Chain Conformations Under Deformation and Constant-strainsupporting
confidence: 83%
“…N = 500 chains orient nearly affinely during strain: ǫ ef f ≃ǫt, while short chains orient much less. The solid lines are far more consistent with both experiments [3][4][5] and simulations [6,7], which show relaxation slows dramatically upon cessation of active deformation. Figure 3 shows simulation data for ǫ ef f (t) under the same procedure of compression followed by constantstrain relaxation.…”
Section: E Chain Conformations Under Deformation and Constant-strainsupporting
confidence: 83%
“…It was also shown that this different partitioning could be the main reason for the enhanced dynamics for the polymer rejuvenated samples. These results are supported by the recent MD simulations of Riggleman et al [14,15] who observed the acceleration of the segmental dynamics under deformation and corresponding changes in the potential energy landscape. Warren and Rottler showed recently [16] that both dynamics and mechanical shift factors change by the same relative amount with aging time and applied stress.…”
Section: Introductionsupporting
confidence: 78%
“…We measure our effective relaxation times during "time windows" as our systems undergo physical aging to equilibrium following approaches used in previous non-equilibrium simulations of the same polymer glass. [34][35][36] Briefly, we divide our simulation trajectory into overlapping windows of fixed widths in time δt win = 200 τ LJ . In each window, we calculate F s (q, t) at q = 7.14, which is approximately the location of the first peak in the static structure factor for this system at equilibrium.…”
Section: Methodsmentioning
confidence: 99%